An Evaluation of the Antimicrobial Activity of Various Concentrations of Ocimum sanctum Against Various Species of Bacteria: an Invitro Study - Shiju Mathew (Institute of Advanced Engineering and Science, 2014)
Plants are one of the most important sources of medicines. Among the plants known for medicinal value, the plants of genus Ocimum belonging to family Labiatae are very important for their therapeutic potentials. Ocimum sanctum L., known as ‘Tulsi’ in Hindi and ‘Holy Basil’ in English is an erect softy hairy aromatic herb or under shrub found throughout India. The antimicrobial activity is done by using Soxhlet apparatus method. For antimicrobial activity, Nutrient broth was used for inoculating the culture. Then wells were cut on the solidified agar medium which were swabbed with microorganism. Thus agar well diffusion method is carried out. The extracts were poured into the wells at different concentrations like 25%, 50% and 100%. After incubation, zone of inhibition was observed. So Ocimum sanctum can be used in developing drugs and medicines against various activities of Bacteria